Herbaceous vegetation communities around lake Manyara, Tanzania: response to environmental gradients - Gideon A. Mseja; Beatrice B. Furael; Gastor J. Lyakurwa; Emanuel H. Martin (Nature Conservation Research: Заповедная наука, 2020)
Healthy populations of wildlife require quality forage sufficiently available in both space and time. The herbaceous vegetation around rift valley lakes in Tanzania varies along productivity, disturbance and stress gradients. We have analysed herbaceous vegetation communities and ascertained the nature of their association with environmental variables around Lake Manyara in Kwakuchinja Wildlife Corridor. The transect method was used for sampling vegetation data. Environmental variables including soil pH, available soil phosphorus, distance from the lakeshore, bare soils, soil water, soil salinity and soil total nitrogen were used as possible explanatory variables. Ordination was used to assemble the herbaceous plant communities and relate with the determined environmental variables. The Shannon-Wiener Index was employed to determine species diversity in each plant community. The results revealed three distinct grassland communities named after the dominant and subdominant species: Sporobolus spicatus, Sporobolus ioclados – S. spicatus and Cynodon dactylon. The Monte Carlo Permutation test revealed that soil pH, available soil phosphorus, distance from the lakeshore and bare soil significantly correlated with herbaceous plant community assemblages. The indices of plant species richness and diversity reflected the influence of soil saturation gradients on plant communities. This study contributes to understanding spatial patterns of herbaceous plant communities around alkaline-saline lakes of the Gregory rift valley in East Africa. It also reveals an association between plant community structures with varying edaphic gradients. We conclude that our study forms the basis for monitoring herbaceous plant community change based on determined environmental variables in the corridors of wildlife conservation areas.